Sosialisasi Gemar Menabung Sedari Dini bagi Siswa Sekolah Dasar di Desa Perkebunan Gunung Melayu - Dinda Fadila Asih; Salman Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
The Community Service Program (KKN) is the answer for students to face these challenges. Elementary school students' awareness of saving is still relatively low. Many students prefer to spend their pocket money on momentary desires rather than saving it. This condition indicates that financial literacy in children is still limited. The main objective of this socialization activity is carried out with an approach that is appropriate to the age of elementary school children, for example, such as games, simulations, or simple counseling. By using such methods, students not only understand the concept of saving, but also have a desire to do it. In addition, this socialization activity instills an attitude of independence and discipline. The socialization program was held as an effort to provide insight and instill awareness to students of Elementary School 014662, Gunung Melayu Plantation Village, Rahuning District, Asahan Regency, and was attended by students in grades 4, 5, and 6 regarding the benefits of saving. To facilitate student understanding, the team demonstrated the practice of saving by using piggy banks and money as concrete examples. After students received material on the importance of saving, the activity continued with a quiz session to increase enthusiasm and test their understanding of the newly presented material. The socialization of the love of saving program, carried out through the Community Service Program (KKN), has proven to be effective in fostering understanding and awareness among elementary school students about the importance of saving from an early age.